Solid-state versus solution investigation of a luminescent chiral BINOL-derived bisphosphate single-molecule magnet. Issue 4 (22nd December 2020) - Mattei, Carlo Andrea; Montigaud, Vincent; Gendron, Frédéric; Denis-Quanquin, Sandrine; Dorcet, Vincent; Giraud, Nicolas; Riobé, François; Argouarch, Gilles; Maury, Olivier; Le Guennic, Boris; Cador, Olivier; Lalli, Claudia; et al.
Abstract : The enantiopure coordination polymer [Dy(hfac)3 (( S / R )-L )] n ([( S / R )-1] n ) involving a BINOL-derived bisphosphate ligand ( S / R )-L is investigated both in solution and solid-state. Abstract : The enantiopure coordination polymer [Dy(hfac)3 (( S / R )-L )] n ([( S / R )-1] n ) involving a BINOL-derived bisphosphate ligand ( S / R )-L is reported. Paramagnetic NMR and computational investigations demonstrated the formation of mononuclear species [( S / R )-1] in CH2 Cl2 solution and its optimized structure was determined. The experimental electronic circular dichroism signals of ( S / R )-L were strongly enhanced after metal coordination [( S / R )-1] . Both polymeric and mononuclear structures displayed field-induced Single-Molecule Magnet (SMM) behaviour with similar multi-relaxation processes due to the retention of crystal-field splitting determined by CASSCF calculations, despite the strong structural transformation between the two media. The HOMO → LUMO transition of the ( S )-L ligand induced the classical Dy(iii ) emission at 77 K that was correlated with the magnetic properties. [( S )-1] n is described as one-dimensional assembly of chiral luminescent Single-Ion Magnets (SIMs).